Dissecting photosynthetic electron transport and photosystems performance in Jerusalem artichoke (Helianthus tuberosus L.) under salt stress - Yan, Kun; Mei, Huimin; Dong, Xiaoyan; Zhou, Shiwei; Cui, Jinxin; Sun, Yanhong (Frontiers in Plant Science, 2022)
Jerusalem artichoke (Helianthus tuberosus L.), a vegetable with medical applications has strong adaptability to marginal barren land, but the suitability as a planting material in saline land remains to be evaluated. This study was envisaged to examine salt tolerance in Jerusalem artichoke from the angel of photosynthetic apparatus stability by dissecting photosynthetic electron transport process. Potted plants were exposed to salt stress by watering nutrient solution supplemented with NaCl. Photosystem I (PSI) and photosystem II (PSII) photoinhibition appeared under salt stress, according to the significant decrease in the maximal photochemical efficiency of PSI (△MR/MR0) and PSII. Consistently, leaf H2O2 concentration and lipid peroxidation were remarkably elevated after 8 days of salt stress, confirming salt-induced oxidative stress. Besides photoinhibition of PSII reaction center, PSII donor side was also impaired under salt stress, as a K step emerged in prompt chlorophyll transient, but PSII acceptor side was more vulnerable, considering the decreased probability for an electron movement beyond primary quinone (ETo/TRo) upon depressed upstream electron donation. The declined performance of entire PSII components inhibited electron inflow to PSI, but severe PSI photoinhibition was not averted. Notably, PSI photoinhibition elevated excitation pressure of PSII (1-qP) by inhibiting PSII acceptor side due to the negative and positive correlation of △MR/MR0 with 1-qP and ETo/TRo, respectively. Excessive reduction of PSII acceptors side due to PSI photoinhibition was simulated by applying specific inhibitor blocking electron transport beyond primary quinone, demonstrating that PSII photoinhibition was actually accelerated by PSI photoinhibition under salt stress. In conclusion, PSII and PSI vulnerability were proved in Jerusalem artichoke under salt stress, and PSII inactivation which was a passive consequence of PSI photoinhibition hardly helped protect PSI. As a salt sensitive species, Jerusalem artichoke was recommended to be planted in non-saline marginal land or mild saline land with soil desalination measures.